2018
DOI: 10.3389/fbioe.2018.00169
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the Effect of Selected Non-Saccharomyces Species on Wine Ecosystem Function and Major Volatiles

Abstract: Natural alcoholic fermentation is initiated by a diverse population of several non-Saccharomyces yeast species. However, most of the species progressively die off, leaving only a few strongly fermentative species, mainly Saccharomyces cerevisiae. The relative performance of each yeast species is dependent on its fermentation capacity, initial cell density, ecological interactions as well as tolerance to environmental factors. However, the fundamental rules underlying the working of the wine ecosystem are not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 61 publications
(107 reference statements)
2
33
0
Order By: Relevance
“…Thus, our data show that production of major volatiles is significantly affected by the yeast species composition and the ecological interactions among the species rather than temperature and SO 2. This result is in agreement with our previous work by Bagheri et al 13 , who confirmed that the aromatic profile of wine is significantly affected by the presence of some non-Saccharomyces (e.g. C. parapsilosis) in grape juice, irrespective of their rapid declines at an early stage of fermentation.…”
Section: Ns-sc-t15-s30supporting
confidence: 94%
See 2 more Smart Citations
“…Thus, our data show that production of major volatiles is significantly affected by the yeast species composition and the ecological interactions among the species rather than temperature and SO 2. This result is in agreement with our previous work by Bagheri et al 13 , who confirmed that the aromatic profile of wine is significantly affected by the presence of some non-Saccharomyces (e.g. C. parapsilosis) in grape juice, irrespective of their rapid declines at an early stage of fermentation.…”
Section: Ns-sc-t15-s30supporting
confidence: 94%
“…During the fermentation process, and dependent on the specific microbiota composition of each must, weakly fermentative yeast species such as Pichia terricola, Metschnikowia pulcherrima and Hanseniaspora uvarum are usually replaced by more strongly fermentative species such as Lachancea thermotolerans and Torulaspora delbrueckii, while Saccharomyces cerevisiae will generally complete the process when alcohol levels are high and oxygen is depleted [5][6][7][8][9][10] . Many of these weakly and more strongly fermentative species, however, can contribute significantly to the final composition of wine, and impact the sensory perception of the product [11][12][13] . The contribution of each individual species will depend on its numerical presence and length of persistence throughout alcoholic fermentation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, S. bacillaris (formerly known as Candida zemplinina) is often isolated from wine fermentations and grapes (Grangeteau et al, 2016;Magyar & Toth, 2011). It has been studied as a possible costarter of wine fermentations, where it contributes to a lower ethanol concentration and a higher glycerol content in the final product (Bagheri, Zambelli, Vigentini, Bauer, & Setati, 2018;Binati et al, 2019;Castrillo, Rabunal, Neira, & Blanco, 2019;Englezos et al, 2016;Englezos et al, 2018;Lemos Junior et al, 2019). S. bombicola is the best-studied species in the W/S clade as it is used for the industrial production of sophorolipids, a class of environmentally friendly biosurfactants used in the cleaning and cosmetic industries, as well as for bioremediation of soil pollution by hydrocarbons (Van Bogaert et al, 2013).…”
Section: Biotechnologymentioning
confidence: 99%
“…During the crushing stage, the strategy to bioprotect must as soon as possible at the biochemical level, avoiding undesired microorganisms' metabolism, by inoculating selected starter cultures is increasingly being employed [18]. Indeed, it has been shown that some non-Saccharomyces species support or inhibit the growth of other non-Saccharomyces and Saccharomyces species in multispecies consortiums, and that the relative performance of each yeast species is dependent on its fermentation capacity, initial cell density, and ecological interactions as well as tolerance to environmental factors [58]. A large number of research work has addressed this topic in recent years, most of which focused on the limitation of spoilage occurrence, mainly due to Brettanomyces bruxellensis growth (for reviews, see [17,39,59]).…”
Section: Non-saccharomyces Yeasts Exerting Indirect Bioprotective Effectmentioning
confidence: 99%